2016
DOI: 10.1109/jlt.2016.2577141
|View full text |Cite
|
Sign up to set email alerts
|

Non-Markovian Property of Afterpulsing Effect in Single-Photon Avalanche Detector

Abstract: The single-photon avalanche photodiode(SPAD) has been widely used in research on quantum optics. The afterpulsing effect, which is an intrinsic character of SPAD, affects the system performance in most experiments and needs to be carefully handled. For a long time, afterpulsing has been presumed to be determined by the pre-ignition avalanche. We studied the afterpulsing effect of a commercial InGaAs/InP SPAD (The avalanche photodiode model is: Princeton Lightwave PGA-300) and demonstrated that its afterpulsing… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 35 publications
0
11
0
Order By: Relevance
“… 19 provides evidence for the hyperbolic sinc model. Recently 26 showed that the afterpulse probability is dependent on past events–a property not considered in the exponential, power, or hyperbolic sinc models. By comparing previously reported results to our own, we realize that there is a large variation between the different commonly used manufactures/makes of detectors and between individual detectors.…”
Section: Discussionmentioning
confidence: 99%
“… 19 provides evidence for the hyperbolic sinc model. Recently 26 showed that the afterpulse probability is dependent on past events–a property not considered in the exponential, power, or hyperbolic sinc models. By comparing previously reported results to our own, we realize that there is a large variation between the different commonly used manufactures/makes of detectors and between individual detectors.…”
Section: Discussionmentioning
confidence: 99%
“…These afterpulses will trigger more afterpulses later, and eventually contribute to a large number of afterpulses. This phenomenon is usually called the higher-order afterpulsing effect [18]. When active quenching is added with high-frequency gated-passive quenching, it can maintain the excess bias at a value below break down voltage for a short period of time, e.g., the first tens of nanoseconds, which physically closes the following tens of gates after an avalanche event and prevents the release of afterpulses within these gates.…”
Section: Methodsmentioning
confidence: 99%
“…For more information, see https://creativecommons.org/licenses/by/4.0/ The proposed counting model generalizes known approaches that only consider dead time [23], [24] by incorporating afterpulsing and twilight pulsing. Afterpulsing is also generalized [25], [26], being treated as a translated point process [27]. A Monte Carlo simulation algorithm is provided [22] that accurately reproduces desired counting statistics under stated assumptions [28], [29].…”
Section: The Contribution Of This Papermentioning
confidence: 99%
“…Each type of trap has its own exponential decay rate γ, its occurrence density in the material and a certain probability of being populated (we assume a constant avalanche charge). These traps work independently [26], which means that after each detection, the set of n AP populated traps {γ k } n AP k=1 is a realization of an inhomogeneous Poisson point process with intensity ρ(γ). This allows for both discrete and continuous spectra of γ (see the Suppl.…”
Section: Point Process Formulationmentioning
confidence: 99%
See 1 more Smart Citation